AB102. Therapeutic potential of adipose-derived stem cells-based micro-tissues in a rat model of stress urinary incontinence - Li, Meng (Transl Androl Urol, 2016)
OBJECTIVE: Traditional two-dimensional (2D) cell culture of adipose-derived stem cells (ADSCs) to halt stress urinary incontinence (SUI) progression have low retention rate and limited function recuperation poorly mimicking in vivo conditions. This study aims to examine the potential and mechanism of three-dimensional (3D) cultures of ADSCs in the treatment of SUI in a rat model simulating childbirth injury. METHODS: ADSCs were used to generate microtissues (MTs) with a hanging drop method. A total of 48 postpartum Sprague-Dawley rats were developed SUI models by 4 hours vagina dilation (VD) followed by bilateral ovariectomy (OV). Ten rats underwent sham OV without VD served as control group. The SUI rats were divided into three groups and received urethral injection of PBS, ADSCs and MTs. Specimens were harvested for histology examination and ADSCs tracking at day 1, 3, 7, 28 (n=3) post-injection. At day 28, the remaining rats were examined for voiding function. Western blot, immunofluorescence and immunohistochemistry staining were performed to examine histological changes and cytokines expression. RESULTS: The voiding function and histopathological structures were better recovered in MTs group than those in ADSCs group. Compared with ADSCs, MTs express higher level of vascular endothelia growth factor (VEGF), TNFα stimulated gene/protein 6 (TSG-6) in vitro and represented a higher retention rate in vivo. CONCLUSIONS: Urethral injection of MTs better restored the voiding function than ADSCs.